Prototyping a peer-to-peer session initiation protocol user agent - Tsietsi, Mosiuoa Jeremia (Rhodes University, Faculty of Science, Department of Computer Science, 2008)
The Session Initiation Protocol (SIP) has in recent years become a popular protocol for the exchange of text, voice and video over IP networks. This thesis proposes the use of a class of structured peer to peer protocols - commonly known as Distributed Hash Tables (DHTs) - to provide a SIP overlay with services such as end-point location management and message relay, in the absence of traditional, centralised resources such as SIP proxies and registrars. A peer-to-peer layer named OverCord, which allows the interaction with any specific DHT protocol via the use of appropriate plug-ins, was designed, implemented and tested. This layer was then incorporated into a SIP user agent distributed by NIST (National Institute of Standards and Technology, USA). The modified user agent is capable of reliably establishing text, audio and video communication with similarly modified agents (peers) as well as conventional, centralized SIP overlays.
Keywords: Computer networks; Computer network protocols -- Standards; Data transmission systems -- Standards; Peer-to-peer architecture (Computer networks); Computer network architectures